Her beauty & her terror : portrait of an archetypal land - Frantom, Michelle (Curtin University, 2014)
This project is comprised of two complementary elements: a discursive exegesis and a production of artwork. Together they explore the idea that by applying Jung's method of 'active imagination', image-making operates as a practice for consciousness that not only enriches the relationship between humans and the non-human world, but reveals new insights into the nature of reality. The studio research was conducted at The Gap, a spectacular wild-site on the south coast of Western Australia.